Little piggies : "This little piggy" and "Pat-a-cake" - Coan, Sharon (Huntington Beach, CA : Teacher Created Materials, 2011)
A readers' theater script for six characters in which five little pigs make sandwiches and cake.
"TCM 13429"--Back cover.
1.4
K-3
K-3
Keywords: Readers' theater; Oral reading; Readers' theater; Readers' theater; Books and reading; Nursery rhymes